Synergic disorders in the early operation of the Szeged Regional Waste Management Program ISPA project - Szabó Ferenc (2009)
On the basis of a case study I present the experiences of the operation and the typical operational conflicts of the completed Hungarian EU environmental infrastructure development projects, first of all concerning the cooperation of the beneficiary local governments. In the analyzed case - "Szeged Regional Waste Management Program" ISPA project - the legal beneficiary is the municipality of Szeged, but the other 32 municipalities of the region are also interested in the successful implementation of the project and are responsible for the continuous long run operation.